The contribution of forensic odontology in the Highland Towers Condominium disaster - Alhabshi, S.F.; Nambiar, P. (1995)
An apartment complex collapsed in Malaysia killing 48 people trapped inside. The dental disaster victim identification team comprising of officers from the Kuala Lumpur General Hospital, Armed Forces and the Dental Faculty, University of Malaya played a very active role in the identification process. Most of the bodies were badly decomposed and some grossly disfigured. Problems were encountered due to inadequate facilities and equipments at the mortuary. Difficulties were also encountered during the procurement and deciphering of information from dental records. Suggestions have been made to improve facilities, expertise and also to create awareness amongst dentists to ensure proper recording of their patients'dental status.